2014
DOI: 10.1371/journal.pone.0103513
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in Sleep and Daytime Sleepiness in Postpartum Women

Abstract: Sleep disruption strongly influences daytime functioning; resultant sleepiness is recognised as a contributing risk-factor for individuals performing critical and dangerous tasks. While the relationship between sleep and sleepiness has been heavily investigated in the vulnerable sub-populations of shift workers and patients with sleep disorders, postpartum women have been comparatively overlooked. Thirty-three healthy, postpartum women recorded every episode of sleep and wake each day during postpartum weeks 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
0
31
4
1
Order By: Relevance
“…Compared to existing evidence that middle-class postpartum women sleep just over 7 hours per night with the longest episode of sleep of 4.1 hours (Filtness et al, 2014; Montgomery-Downs et al, 2010), women in our sample obtained dramatically less total sleep (5.5 hours) and the longest period of sleep was much shorter (2.8 hours). Chronic short sleep duration has significant implications to physical and mental health, functioning and performance and safety in everyday life (Watling et al, 2016).…”
Section: Clinical Nursing Implicationscontrasting
confidence: 97%
See 1 more Smart Citation
“…Compared to existing evidence that middle-class postpartum women sleep just over 7 hours per night with the longest episode of sleep of 4.1 hours (Filtness et al, 2014; Montgomery-Downs et al, 2010), women in our sample obtained dramatically less total sleep (5.5 hours) and the longest period of sleep was much shorter (2.8 hours). Chronic short sleep duration has significant implications to physical and mental health, functioning and performance and safety in everyday life (Watling et al, 2016).…”
Section: Clinical Nursing Implicationscontrasting
confidence: 97%
“…This same study found that 46% of women napped on average for 2.2 hours per day at week 4. In another study, 44 new mothers slept on average 7.4 hours at night and the longest nighttime sleep episode was on average 4.1 hours in week 6 (Filtness, MacKenzie, & Armstrong, 2014). Both studies were conducted in women who were primarily Caucasian, middle-class, and college educated.…”
mentioning
confidence: 99%
“…One recent study suggests that over half of new mothers continue to suffer from excessive daytime sleepiness eighteen weeks after delivery, with implications for daytime functioning and timing of the return to the workforce. 46 Also, there is evidence to suggest that both pregnancy-associated and postpartum disordered sleep patterns can impact on postnatal depression. A study using wrist actigraphy to monitor poor sleep maintenance and looking at subjective assessments of sleep in twenty-five healthy primiparous women found that poor sleep maintenance was significantly associated with depression.…”
Section: Post-partum Sleep Disordersmentioning
confidence: 99%
“…A crying infant in the vehicle might be a significant distracting factor for a mother, as the primary function of crying is to get attention from caregivers. 13 The mothers of small children may also be exposed to sleep disruption and fatigue 14,15 and preliminary results suggest that new mothers' sleep problems might be linked to a higher crash risk 16,17 . In addition, over 10% of mothers suffer from postpartum depression.…”
Section: Introductionmentioning
confidence: 99%